Morphological diversification with emphasis on the structural and homology patterns of male genitalia in genus Limnebius (Leach 1815; Hydraenidae: Coleoptera) - Rudoy, Andrey [UNESP]; Meng, Ling-Zeng (Oxford University Press (OUP), 2024)
Limnebius exhibits uniform external appearance but variable male genitalia: from differently curved rod shapes in the subgenus Bilimneus to up to seven longitudinally separated folds or appendages in Limnebius s.s.. Among nonsexual traits, two subgenera diverge only in the wing. The aedeagal complexity in Limnebius s.s. is associated with the secondary sexual structures on the abdomen and metatibia; larger body size, which forms two clusters; and male-biased sexual dimorphism. To cluster the subdivisions with phylogenetically unresolved relationships, we examined the coincidence of the traits in both sexes, based on the premise of the independent and monophyletic origin of histologically unsimilar elements. The folds and additional appendages on the median lobe, abdominal paired rows of setae, and protuberances show that the L. parvulus and L. nitidus groups have maximum aedeagal complexity in the L. parvulus and L. nitiduloides subgroups, respectively. The L. parvulus group exhibits a gradual increase in the number of elements of the aedeagi. The histology of connections of the parameres and additional appendages to the median lobe, along with that of the flagellum opening, reveal the subgroups’ relationship in the L. nitidus group, as well as a decrease in the complexity of the male genitalia in their recent branches.
Keywords: evolution; genitalia anatomy; homology; Hydraenidae; Limnebius; morphological comparison; phylogenetics; sibling species